2001
DOI: 10.1203/00006450-200102000-00019
|View full text |Cite
|
Sign up to set email alerts
|

BMI in Childhood and Its Association with Height Gain, Timing of Puberty, and Final Height

Abstract: No large population-based study has addressed the question of how overnutrition is related to subsequent height gain in childhood, timing of puberty, and final height. The present data represent a large Swedish population-based longitudinal growth study. Height gain in childhood, timing of reaching peak height velocity and height gain during adolescence, and final height were regarded as the short-term, interim, and long-term outcomes of childhood nutritional status, i.e. body mass index (BMI) change between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

50
265
10
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(339 citation statements)
references
References 23 publications
50
265
10
14
Order By: Relevance
“…The growth study based on the GrowUp 1974 Gothenburgbirth cohort found somewhat similar results; a greater increase in BMI from 2−8 y of age was associated with a taller stature at 8 y (19). Our study also confirmed results from many studies tracking childhood obesity back to birth (20,21), with significant differences in birth-weight between children who went on to have higher BMIs during childhood compared with children with BMIs in the normal/underweight range.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The growth study based on the GrowUp 1974 Gothenburgbirth cohort found somewhat similar results; a greater increase in BMI from 2−8 y of age was associated with a taller stature at 8 y (19). Our study also confirmed results from many studies tracking childhood obesity back to birth (20,21), with significant differences in birth-weight between children who went on to have higher BMIs during childhood compared with children with BMIs in the normal/underweight range.…”
Section: Discussionsupporting
confidence: 87%
“…However, most other non-American studies support our findings, with earlier onset of puberty in overweight/ obese boys; in the 1940s, under-nutrition was reported to delay onset of puberty and Mossberg found earlier puberty in obese Swedish boys. These findings were confirmed in the United Kingdom (18), and later in many European counties (19,25,30), and Japan (31). Correlation between BMI and mid-puberty was also seen for boys in a UK study, which found a linear correlation between BMI SDS in childhood and age at PHV (30).…”
Section: Discussionmentioning
confidence: 59%
“…Contemporary children are more obese, and the results of several studies have found that BMI exerts a negative effect on the height gain during puberty (11,12). We found no evidence of this relationship after analyzing our data, and we attribute this finding to the very small number of obese children in the study population: only five boys and four girls had a BMI above the 90th percentile.…”
Section: Discussioncontrasting
confidence: 60%
“…Although grouping adolescents by Tanner stage is interesting, determining the Tanner stage is difficult in large surveys. Additionally, overweight may affect sexual development, inducing acceleration in girls and delay in boys (He and Karlberg, 2001). Compared with Chilean 50th, 85th and 95th percentiles of BMI for age, Mexican boys and girls have higher BMI levels.…”
Section: Mexican Anthropometric Percentiles In Adolescentsmentioning
confidence: 99%